Carbon-rich nanostructures: The conversion of acetylenes into materials - Chernick, Erin; Tykwinski, Rik (Journal of Physical Organic Chemistry, 2013)
The inherent thermodynamic instability of the carbon-carbon triple bond offers a unique starting point for the formation of carbon-rich nanomaterials, which are of increasing importance for use in materials science and technology. Whereas significant efforts have recently been devoted toward suppressing the well-known reactivity of sp-hybridized compounds in an effort to obtain the elusive carbon allotrope "carbyne," this mini-review will focus on the opposite idea; that is, we explore current research efforts that attempt to harness the reactivity of carbon-carbon triple bonds in a controlled, templated manner that ultimately converts acetylenic precursors into ordered, carbon-based nanomaterials. Copyright © 2013 John Wiley & Sons, Ltd.

Interplay between Solution Processing and Electronic Structure in Metal-Free Organic Magnets Based on a TEMPO Pentacene Derivative - Arantes, C.; Chernick, Erin; Gruber, Marco; Rocco, M. L. M.; Chasse, T.; Tykwinski, Rik; Casu, M. B. (Journal of Physical Chemistry C, 2016)
We have used X-ray photoelectron spectroscopy (XPS) to describe the electronic structure of two newly synthesized derivatives of the 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS-PEN) carrying the 2,2,6,6-tetramethylpiperidin-1-yl)oxidanyl (TEMPO) radical as a substituent. XPS results underline the existing interplay between electronic structure and preparation methods. Our observations suggest a strong influence of the film processing on the shakeup satellite intensities of the N 1s core level spectra. Preparation methods, by tuning the different degree of intermolecular screening, may be use as a tool to influence the properties and the behavior of these materials as thin films, including their local magnetic-exchange coupling.
EAM Import::2019-03-13

Optically pure, monodisperse cis-oligodiacetylenes: Aggregation-induced chirality enhancement - Chernick, Erin; Börzsönyi, Gabor; Steiner, Christian; Ammon, Maximilian Michael; Geßner, David; Frühbeißer, Sabine; Gröhn, Franziska; Maier, Sabine; Tykwinski, Rik (Angewandte Chemie International Edition, 2014)
Conformational changes in the conjugated backbone of poly- and oligodiacetylenes (PDAs and ODAs) play an important role in determining the electronic properties of these compounds. At the same time, conformational changes can also result in a folded structure that shows helical chirality. Using D-camphor as a chiral building block, we have designed a high-yielding, iterative synthesis of monodisperse, optically pure cis-oligodiacetylenes (ODAs). cis-ODAs up to the tridecamer have been formed, which is the longest monodisperse cis-ODA reported to date. UV/Vis spectroscopy suggests a large effective conjugation length in THF, likely the result of a linear, planar conformation in this solvent. High-resolution STM/AFM measurements of the nonamer cast from THF onto HOPG show a linear structure. In iPrOH, circular dichroism (CD) spectra suggest the formation of chiral aggregates for ODAs with at least nine D-camphor units, based on a strong CD response. Conformation, conjugation: A series of optically pure, monodisperse cis-oligodiacetylenes (cis-ODAs) based on D-camphor building blocks has been synthesized up to the tridecamer length, which represents the longest cis-ODA reported to date. Optical spectroscopy and STM/AFM measurements indicate that the oligomers assume a linear, planar conformation in THF. Conversely, in iPrOH solution ODAs with n≥9 form chiral aggregates. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Pentacene Appended to a TEMPO Stable Free Radical: The Effect of Magnetic Exchange Coupling on Photoexcited Pentacene - Chernick, Erin; Casillas, Ruben; Zirzlmeier, Johannes; Gardner, Daniel M.; Gruber, Marco; Kropp, Henning; Meyer, Karsten; Wasielewski, Michael R.; Guldi, Dirk Michael; Tykwinski, Rik (Journal of the American Chemical Society, 2015)
Understanding the fundamental spin dynamics of photoexcited pentacene derivatives is important in order to maximize their potential for optoelectronic applications. Herein, we report on the synthesis of two pentacene derivatives that are functionalized with the [(2,2,6,6-tetramethylpiperidin-1-yl)oxy] (TEMPO) stable free radical. The presence of TEMPO does not quench the pentacene singlet excited state, but does quench the photoexcited triplet excited state as a function of TEMPO-to-pentacene distance. Time-resolved electron paramagnetic resonance experiments confirm that triplet quenching is accompanied by electron spin polarization transfer from the pentacene excited state to the TEMPO doublet state in the weak coupling regime.
EAM Import::2019-03-08

Singlet fission in pentacene dimers - Zirzlmeier, Johannes; Lehnherr, Dan; Brana Coto, Pedro; Chernick, Erin; Casillas, Ruben; Basel, Bettina; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Singlet fission (SF) has the potential to supersede the traditional solar energy conversion scheme by means of boosting the photon-to-current conversion efficiencies beyond the 30% Shockley-Queisser limit. Here, we show unambiguous and compelling evidence for unprecedented intramolecular SF within regioisomeric pentacene dimers in room-temperature solutions, with observed triplet quantum yields reaching as high as 156 ± 5%. Whereas previous studies have shown that the collision of a photoexcited chromophore with a ground-state chromophore can give rise to SF, here we demonstrate that the proximity and sufficient coupling through bond or space in pentacene dimers is enough to induce intramolecular SF where two triplets are generated on one molecule.

Solution-based intramolecular singlet fission in cross-conjugated pentacene dimers - Zirzlmeier, Johannes; Casillas, Ruben; Reddy, Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Chernick, Erin; Papadopoulos, Ilias; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Nanoscale, 2016)
We show unambiguous and compelling evidence by means of pump-probe experiments, which are complemented by calculations using ab initio multireference perturbation theory, for intramolecular singlet fission (SF) within two synthetically tailored pentacene dimers with cross-conjugation, namely XC1 and XC2. The two pentacene dimers differ in terms of electronic interactions as evidenced by perturbation of the ground state absorption spectra stemming from stronger through-bond contributions in XC1 as confirmed by theory. Multiwavelength analysis, on one hand, and global analysis, on the other hand, confirm that the rapid singlet excited state decay and triplet excited state growth relate to SF. SF rate constants and quantum yields increase with solvent polarity. For example, XC2 reveals triplet quantum yields and rate constants as high as 162 ± 10% and (0.7 ± 0.1) × 1012 s-1, respectively, in room temperature solutions.
EAM Import::2019-03-13